Hospitalitas Kristen sebagai Landasan Relasi Mayoritas-Minoritas di Desa Segaran, Kecamatan Wates, Kediri - Yuangga Yahya; Intan Baeduri; Asyreqa Najma (Reformed Center for Religion and Society, 2022)
This study aims to describe the concepts of hospitality and friendship in practice in Segaran village, Wates, Kediri. The village has a Christian majority population, a minority Muslim population, and adherents of other religions. The research in this village was conducted by qualitative research with Corbin and Strauss’s grounded theory design. Data collection was conducted through observation, interviews, and documentation. The data will be analyzed descriptively and interpreted using the structural functionalism theory of Durkheim. This study shows that majority-minority relations in Segaran village can be fair and equal. The Christians had internalized the Christianity teaching of hospitality and friendship towards the Muslims in Segaran. It is reinforced by the existence of religious and social institutions, social facts, and social interactions based on the teachings of hospitality so that religious values ​​can show an integrative and adhesive function for the entire community in Segaran.